2010
DOI: 10.1037/a0020280
|View full text |Cite
|
Sign up to set email alerts
|

Predicting behavior in economic games by looking through the eyes of the players.

Abstract: Social scientists often rely on economic experiments such as ultimatum and dictator games to understand human cooperation. Systematic deviations from economic predictions have inspired broader conceptions of self-interest that incorporate concerns for fairness. Yet no framework can describe all of the major results. We take a different approach by asking players directly about their self-interest--defined as what they want to do (pleasure-maximizing options). We also ask players directly about their sense of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 80 publications
0
34
1
Order By: Relevance
“…The dictator game is a variation of the ultimatum game, in which "proposers" can divide a certain amount of money between themselves and "receivers," without the fear of not getting the money, due to a rejection by the receiver and without having to make strategic considerations (for further details, see Güth, 1995;Haselhuhn & Mellers, 2005;Hewig et al, 2011;Kahneman et al, 1986;Mellers et al, 2010;Weiland et al, 2012). Accordingly, it has been suggested that increased offers in the dictator game are motivated altruistically, especially if these offers can be given anonymously.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The dictator game is a variation of the ultimatum game, in which "proposers" can divide a certain amount of money between themselves and "receivers," without the fear of not getting the money, due to a rejection by the receiver and without having to make strategic considerations (for further details, see Güth, 1995;Haselhuhn & Mellers, 2005;Hewig et al, 2011;Kahneman et al, 1986;Mellers et al, 2010;Weiland et al, 2012). Accordingly, it has been suggested that increased offers in the dictator game are motivated altruistically, especially if these offers can be given anonymously.…”
Section: Discussionmentioning
confidence: 98%
“…1995; Haselhuhn & Mellers, 2005;Kahneman, Knetsch, & Thaler, 1986;Mellers et al, 2010). In the dictator game, a "proposer" has to divide a certain amount of money between herself or himself and a "receiver," whereby the "receiver" has no options to react to the division, which was made by the "proposer," in contrast to the ultimatum game (for a more detailed overlook, see, e.g., Camerer, 2003;Hewig et al, 2011).…”
mentioning
confidence: 97%
“…Since humans must commonly make decisions within a social context, it is important to explore the factors that influence our social decision-making. It has been found that social interactions are driven not only by logic (Camerer, 1997; Burks et al, 2003; DeSteno et al, 2010) but also by factors such as descriptive framing (Camerer, 1997; De Martino et al, 2006), fairness equilibrium (Camerer, 1997), consideration of the beliefs and desires of other players (Dubey et al, 1987; Mellers et al, 2010), perceived trustworthiness (Cox, 2004; King-Casas et al, 2005; Charness et al, 2011), and other aspects of the players' perceived character (De Dreu and McCusker, 1997). Moreover, social decision-making is influenced by our emotions (Frank, 1988; Elster, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These tokens are later converted into real earnings. Such economic games provide important insights into the roles of reciprocity [9], [10], reputation [10], [25], punishment [12], [13], between-group competition [26], [27], negotiation [28] and fairness norms [29] in maintaining cooperation. Experiments have also demonstrated individual [18], [30], cultural [31][33] and sex-based [34] differences in cooperative strategies.…”
Section: Introductionmentioning
confidence: 99%